A PDA-PANI-Ti3C2T x Waterborne polyurethane anticorrosive coating and preparation method thereof
By adding PDA-PANI-Ti3C2Tx composite to the water-based polyurethane coating, the problem of insufficient corrosion resistance of water-based polyurethane coating in strong corrosion environments is solved, significantly improving the barrier and mechanical properties of the coating, and achieving long-term corrosion resistance.
Patent Information
- Application Number
- CN202210360454.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-07
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-04-07
AI Technical Summary
The existing water-based polyurethane coatings lack corrosion resistance in strong corrosion environments, and the poor interface compatibility between polyaniline and aqueous resin leads to poor mechanical properties of the composite coating.
The PDA-PANI-Ti3C2Tx (MXene) complex is combined with aqueous polyurethane, and the environmental stability of Ti3C2Tx is enhanced by the co-modification of PDA and PANI, and the defoaming agent, leveling agent and dispersing agent are added to form PDA-PANI-containing Ti3C2Tx's water-based polyurethane anticorrosion coating improves the barrier capability and mechanical properties of the coating.
It significantly improves the barrier ability, mechanical properties and corrosion resistance of the coating, enhances the environmental stability of Ti3C2Tx, avoids the agglomeration of PDA and PANI particles, and improves the long-term corrosion resistance of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer coatings, and particularly relates to a PDA-PANI-Ti 3 C 2 T x (MXene)-based waterborne polyurethane anti-corrosion coating and preparation method thereof. Background Art
[0002] Metal corrosion can be seen everywhere in daily life and industrial production, which has a huge impact on our production and life. According to relevant statistics, the economic losses caused by metal corrosion worldwide exceed 4 trillion US dollars; and metal corrosion will also affect the mechanical properties of metal components, leading to unpredictable safety accidents. In addition, it is difficult to recycle metals after corrosion, resulting in metal waste, and also increasing the loss of metal mineral resources and energy. Therefore, metal corrosion protection is of great value to economic development and production safety. In the past few decades, scientists have studied many anti-corrosion strategies (structural change method, electrochemical method, anti-corrosion coating method, etc.), among which the application of organic polymer coatings on metal surfaces is one of the most convenient, direct and economical methods. Organic coatings are divided into solvent-based coatings and water-based coatings. Solvent-based coatings have good film density and water resistance; however, solvent-based coatings contain a large amount of volatile organic compounds (VOCs), which will cause harm to the environment and human body. Due to people's attention to human health and environmental protection, water-based coatings have attracted widespread attention because of their green, environmentally friendly and pollution-free nature. However, pure water-based coatings will leave water channels after film formation and cannot provide sufficient long-term protection for metal substrates, especially in highly corrosive environments. Organic-inorganic composites are a common method to enhance the corrosion resistance of waterborne polyurethane (WPU) coatings.
[0003] In recent years, a new type of two-dimensional transition metal carbide / nitride (MXene) has good dispersibility in water system and has large surface area and layer barrier properties similar to graphene, showing great corrosion shielding potential. 3 C 2 T x ) is added directly or after modification to water-based resin to enhance the corrosion resistance of water-based resin coating. For example, in the Chinese patent publication CN112552801A, polyaniline is modified to form Ti 3 C 2 T x Directly adding PANI into waterborne acrylic resin can enhance the corrosion resistance of the coating. However, due to the poor interfacial compatibility between PANI and waterborne resin, the composite coating has problems such as poor mechanical properties. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a PDA-PANI-Ti 3 C 2 T x Water-based polyurethane anti-corrosion coating.
[0005] Another object of the present invention is to provide the above-mentioned PDA-PANI-Ti 3 C 2 T x The invention discloses a preparation method of a water-based polyurethane anti-corrosion coating.
[0006] The purpose of the present invention is achieved through the following solutions:
[0007] A PDA-PANI-Ti 3 C 2 T x A water-based polyurethane anti-corrosion coating comprising water-based polyurethane, PDA-PANI-Ti 3 C 2 T x (MXene) composites, defoamers, leveling agents, dispersants, industrial silica sol and other ingredients.
[0008] The PDA-PANI-Ti 3 C 2 T x A water-based polyurethane anti-corrosion coating of (MXene), comprising the following components in parts by mass:
[0009]
[0010] The waterborne polyurethane is selected from F0401 or F0402, both of which can be purchased from Shenzhen Yoshida Chemical Co., Ltd., preferably waterborne polyurethane F0401;
[0011] The industrial silica sol is commercially available, with a solid content of 20-30% and a particle size of 10-20 nm;
[0012] The defoamer is a water-based mineral oil defoamer purchased from Dingsheng Environmental Protection Technology Co., Ltd.
[0013] The leveling agent is an organic silicon leveling agent, preferably AKN-151B, purchased from Foshan Qianyou Chemical Co., Ltd.
[0014] The dispersant is an unsaturated polycarboxylic acid polymer solution, preferably BYK-P104, purchased from BYK Chemical Co., Ltd., Germany.
[0015] A PDA-PANI-Ti 3 C 2 T xThe preparation method of the waterborne polyurethane anticorrosive coating comprises the following steps:
[0016] PDA-PANI-Ti 3 C 2 T x The (MXene) composite dispersion is added to the aqueous polyurethane emulsion and mixed evenly, and then industrial silica sol, defoamer, leveling agent and dispersant are added thereto and mixed evenly to obtain a PDA-PANI-Ti 3 C 2 T x Water-based polyurethane anti-corrosion coating.
[0017] The PDA-PANI-Ti 3 C 2 T x The preparation method of the (MXene) composite dispersion comprises the following steps:
[0018] (1) completely dissolving aniline monomer in hydrochloric acid to obtain an aniline / HCl solution; then completely dissolving ammonium persulfate in hydrochloric acid to obtain an ammonium sulfate / HCl solution;
[0019] (2) Add the aniline / HCl solution in step (1) to Ti 3 C 2 T x Next, the ammonium sulfate / HCl solution in step (1) was added to the mixture for reaction. After the reaction was completed, the mixture was centrifuged to collect the PANI-Ti 3 C 2 T x (MXene) precipitate and wash to remove unreacted aniline monomer;
[0020] (3) Wash the PANI-Ti 3 C 2 T x (MXene) is precipitated and dispersed in water to obtain a dispersion, tromethamine is dissolved in the dispersion, and the pH value of the mixture is adjusted;
[0021] (4) Add dopamine hydrochloride to the mixed solution after adjusting the pH value in step (3) to react. After the reaction is completed, centrifuge and collect the PDA-PANI-Ti 3 C 2 T x The (MXene) solid precipitate was washed to remove the unreacted dopamine hydrochloride, and finally the solid precipitate was dispersed in water to obtain PDA-PANI-Ti 3 C 2 T x (MXene) dispersion.
[0022] The concentration of hydrochloric acid in step (1) is 1 mol / L; the amounts of aniline monomer and hydrochloric acid are such that 0.1 to 0.4 g of aniline monomer is added to every 20 ml of hydrochloric acid; the amounts of ammonium sulfate and hydrochloric acid are such that 0.3 to 1.2 g of aniline monomer is added to every 10 ml of hydrochloric acid;
[0023] Ti described in step (2) 3 C 2 T x The dispersion is Ti 3 C 2 T x Disperse in water and 2 Ultrasonic treatment under protection to obtain 2-4g / L Ti 3 C 2 T x Aqueous dispersion;
[0024] The aniline / HCl solution, ammonium sulfate / HCl solution and Ti 3 C 2 T x The volume ratio of the dispersion was 2:1:10;
[0025] The static condition described in step (2) is to place at 0-8°C for 12-48h;
[0026] The reaction conditions in step (2) are 0-8°C for 12-48h;
[0027] The washing described in step (2) refers to washing the precipitate with water or anhydrous ethanol;
[0028] The amount of water used in step (3) is such that 1000 ml of water is added for every 1 g of precipitation;
[0029] The amount of tromethamine used in step (3) satisfies the following conditions: 1-5 L of dispersion liquid is used for every 1.2-6 g of tromethamine; preferably, 5 L of dispersion liquid is used for every 6 g of tromethamine;
[0030] The pH value in step (3) is adjusted to 8-9 by adding 0.1 mol / L hydrochloric acid;
[0031] The amount of dopamine hydrochloride used in step (4) satisfies: 0.625-3.125 L of the mixed solution is used for every 1-5 g of dopamine hydrochloride; preferably, 0.625 L of the mixed solution is used for every 1 g of dopamine hydrochloride;
[0032] The reaction conditions in step (4) are 4-30° C. for 12-48 h;
[0033] The washing described in step (4) refers to washing the precipitate with water or anhydrous ethanol;
[0034] The PDA-PANI-Ti described in step (4) 3 C 2 T x The (MXene) dispersion is preferably 1 g PDA-PANI-Ti 3 C 2 T x The (MXene) solid precipitate was dispersed in 250 ml of water.
[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0036] (1) The PDA-PANI-Ti 3 C 2 T x (MXene) water-based anti-corrosion coating, adding a small amount of evenly dispersed PDA-PANI-Ti 3 C 2 T x (MXene) composites can significantly improve the barrier capacity, mechanical properties and anti-corrosion capabilities of the coating.
[0037] (2) In the present invention, PDA and PANI are used to 3 C 2 T x The joint modification of (MXene) greatly enhances the Ti 3 C 2 T x (MXene) environmental stability. At the same time, Ti 3 C 2 T x The good dispersibility of (MXene) in water system avoids the 3 C 2 T x The (MXene) complex agglomerates in WPU, solving the problem that PDA and PANI particles are easy to agglomerate in the coating.
[0038] (3) The composite coating synergizes the corrosion inhibition effect of polydopamine and the passivation effect of polyaniline, thereby greatly improving the long-term corrosion resistance of the coating. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0040] Unless otherwise specified, the reagents used in the examples can be purchased from the market.
[0041] The coating performance tests in all embodiments of the present invention were carried out according to the following standards:
[0042] Pencil hardness is measured according to GB / 6739-1996;
[0043] Water resistance is measured according to GB / 1733-1993;
[0044] Acid resistance is measured according to GB / T9274-1988;
[0045] Alkali resistance is measured according to GB / T9274-1988;
[0046] Salt spray resistance is measured according to GB / T1771-2007;
[0047] Example 1
[0048] Preparation of PDA-PANI-Ti 3 C 2 T x (MXene) water-based anti-corrosion coating:
[0049] 10 parts by mass of PDA-PANI-Ti 3 C 2 T x 100 parts by mass of aqueous polyurethane was added to the (MXene) dispersion and stirred for 40 minutes at 500 rad / min to mix evenly. Then 5 parts by mass of industrial silica sol, 1.5 parts of defoamer, 0.5 parts of leveling agent and 0.5 parts of dispersant were added thereto and mixed evenly to obtain a PDA-PANI-TiO2-containing 3 C 2 T x (MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0050] The above-mentioned PDA-PANI-Ti 3 C 2 T x The preparation steps of the (MXene) composite dispersion are as follows:
[0051] (1) First, 0.1 g of aniline monomer was completely dissolved in 20 ml of 1 M hydrochloric acid to obtain an aniline / HCl solution; then 0.3 g of ammonium persulfate was completely dissolved in 10 ml of 1 M hydrochloric acid to obtain an ammonium sulfate / HCl solution.
[0052] (2) Preparation of Ti 3 C 2 T x Dispersion:
[0053] You can purchase Ti 3 C 2 T x and water, and in N 2 The dispersion was then centrifuged at 5000 rpm for 30-60 minutes to collect the upper dispersion to obtain 4 g / L Ti 3 C 2 T x Aqueous dispersion;
[0054] Ti can also be prepared by the following method 3 C 2 T x Aqueous dispersion:
[0055] (a) 3.12 g of LiF and 40.00 ml of 12 M HCl were mixed in a plastic container and stirred at 4-25° C. for 0.5-2 h to form a mixed solution;
[0056] (b) Then 2.0 g Ti 3 AlC 2 The powder is added to the mixed solution in (a), and stirred at 40-60°C for 48.0-72h;
[0057] (c) centrifuging the mixed solution obtained in (b) at a speed of 5000-7000 rpm, collecting the bottom precipitate, transferring it into 100 ml of 2 mol / L HCl and stirring it for 120-360 min;
[0058] (d) Centrifuge the mixed solution after stirring in (c) at 5000 rpm for 5-30 min, pour out the supernatant, and redisperse the precipitate with deionized water. Repeat several times until the pH value of the dispersion is ≥5;
[0059] (e) Dilute the dispersion (d) to 4 g / L with deionized water and 2 The dispersion was then centrifuged at 5000 rpm for 30-60 minutes to obtain the Ti 3 C 2 T x Aqueous dispersion.
[0060] (2) Add 10 ml of aniline / HCl solution to 50 ml of prepared Ti 3 C 2 T x The dispersion was added to the suspension and the mixture was placed at 4°C for 12 hours. Next, 5 ml of ammonium sulfate / HCl solution was added to the suspension and reacted at 4°C for 12 hours. After the reaction, the suspension was centrifuged at 5000 rpm for 5 minutes, and the bottom precipitate was collected and rinsed three times with deionized water to remove the unreacted aniline monomer.
[0061] (3) The precipitate washed in step (2) was ultrasonically dispersed in deionized water, 0.06 g of tromethamine was dissolved in 50 ml of the dispersion, and 0.1 mol / L hydrochloric acid was gradually added to the solution until the pH reached 8.5.
[0062] (4) Then, add 62.5 ml of PANI-Ti after adjusting the pH in step (3) 3 C 2 T x 0.1 g of dopamine hydrochloride was added to the (MXene) mixture; the reaction was continued at 4 °C for 24 h. After the reaction was completed, the suspension was centrifuged at 5000 rpm for 5 min, the bottom precipitate was collected and rinsed three times with deionized water to remove the unreacted dopamine hydrochloride. 3 C 2 T x The (MXene) solid precipitate was added with 0.25 L of deionized water and ultrasonically dispersed for 30 min to obtain 4 mg / ml of PDA-PANI-Ti 3 C 2 T x (MXene) dispersion.
[0063] Example 2
[0064] 20 parts by mass of PDA-PANI-Ti 3 C 2 T x 100 parts by mass of aqueous polyurethane was added to the (MXene) dispersion and stirred for 40 minutes at 500 rad / min to mix evenly. Then 5 parts by mass of industrial silica sol, 0.5 parts of defoamer, 1.5 parts of leveling agent and 0.5 parts of dispersant were added thereto and mixed evenly to obtain a PDA-PANI-TiO2-containing 3 C 2 T x(MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0065] The above-mentioned PDA-PANI-Ti 3 C 2 T x The preparation steps of the (MXene) composite dispersion are consistent with those in Example 1.
[0066] Example 3
[0067] 30 parts by mass of PDA-PANI-Ti 3 C 2 T x 100 parts by mass of aqueous polyurethane was added to the (MXene) dispersion and stirred at 500 rad / min for 40 minutes to mix evenly. Then 7 parts by mass of industrial silica sol, 0.5 parts of defoamer, 0.5 parts of leveling agent and 1.5 parts of dispersant were added thereto and mixed evenly to obtain a PDA-PANI-TiO2-containing 3 C 2 T x (MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0068] The above-mentioned PDA-PANI-Ti 3 C 2 T x The preparation steps of the (MXene) composite dispersion are consistent with those in Example 1.
[0069] Example 4
[0070] 40 parts by mass of PDA-PANI-Ti 3 C 2 T x 100 parts by mass of waterborne polyurethane was added to the (MXene) dispersion and stirred at 500 rad / min for 40 minutes to mix evenly. Then 9 parts by mass of industrial silica sol, 1.0 parts of defoamer, 0.5 parts of leveling agent and 1.0 parts of dispersant were added thereto and mixed evenly to obtain a PDA-PANI-TiO2-containing 3 C 2 T x (MXene) water-based polyurethane anti-corrosion coating. It was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after being maintained at room temperature for 7 days, and its performance is shown in Table 1.
[0071] The above-mentioned PDA-PANI-Ti 3 C 2 T x The preparation steps of the (MXene) composite dispersion are consistent with those in Example 1.
[0072] Example 5
[0073] 50 parts by mass of PDA-PANI-Ti 3 C 2 T x Add 100 parts by mass of waterborne polyurethane to the (MXene) dispersion and stir for 40 minutes at 500 rad / min to mix evenly. Then add 10 parts by mass of industrial silica sol, 1.5 parts of defoamer, 1.5 parts of leveling agent and 1.5 parts of dispersant. Apply it on tinplate and glass sheets and put it in a 35°C oven to form a transparent paint film after the water evaporates. The formed paint film was tested after 7 days of maintenance at room temperature, and its performance is shown in Table 1.
[0074] The above-mentioned PDA-PANI-Ti 3 C 2 T x The preparation steps of the (MXene) composite dispersion are consistent with those in Example 1.
[0075] Comparative Example 1
[0076] 100 parts by mass of waterborne polyurethane, under the condition of 500rad / min, add 10 parts by mass of industrial silica sol, 1.5 parts of defoamer, 1.5 parts of leveling agent, and 1.5 parts of dispersant. Apply it on tinplate and glass sheet, put it in a 35℃ oven, and form a transparent paint film after the water evaporates. The formed paint film is tested after 7 days of maintenance at room temperature, and its performance is shown in Table 1.
[0077] Comparative Example 2
[0078] 20 parts by mass of MXene dispersion (4 g / L Ti 3 C 2 T x 100 parts by mass of waterborne polyurethane was added to the aqueous solution, and 10 parts by mass of industrial silica sol, 1.5 parts of defoamer, 1.5 parts of leveling agent and 1.5 parts of dispersant were added to the aqueous solution at 500 rad / min. The aqueous solution was applied on tinplate and glass sheets and placed in a 35°C oven to form a transparent paint film after the water evaporated. The formed paint film was tested after 7 days of maintenance at room temperature, and its performance is shown in Table 1.
[0079] Table 1 Test results of coating properties obtained according to Examples 1 to 5
[0080]
[0081] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A PDA-PANI-Ti3C2T x The water-based polyurethane anti-corrosion coating is characterized in that It includes the following components by mass: 100 parts of waterborne polyurethane; PDA-PANI-Ti3C2T x (MXene) composite dispersion 10-50 parts; 5-10 parts of industrial silica sol; 0.5-1.5 parts of defoaming agent; 0.5-1.5 parts of leveling agent; Dispersant 0.5-1.5 parts; The waterborne polyurethane is selected from F0401 or F0402; The industrial silica sol is commercially available silica sol with a solid content of 20-30% and a particle size of 10-20 nm; The defoamer is a water-based mineral oil defoamer; The leveling agent is an organic silicon leveling agent; The dispersant is an unsaturated polycarboxylic acid polymer solution; The PDA-PANI-Ti3C2T x The preparation method of the composite dispersion comprises the following steps: (1) completely dissolving aniline monomer in hydrochloric acid to obtain an aniline / HCl solution; then completely dissolving ammonium persulfate in hydrochloric acid to obtain an ammonium sulfate / HCl solution; (2) Add the aniline / HCl solution from step (1) to the Ti3C2T x The aqueous dispersion was allowed to stand; next, the ammonium sulfate / HCl solution in step (1) was added to the mixture for reaction. After the reaction was completed, the mixture was centrifuged to collect the PANI-Ti3C2T x precipitating and washing to remove unreacted aniline monomer; (3) Wash the PANI-Ti3C2T x The precipitate is dispersed in water to obtain a dispersion, tromethamine is dissolved in the dispersion, and the pH value of the mixture is adjusted; (4) Add dopamine hydrochloride to the mixed solution after adjusting the pH value in step (3) to react. After the reaction is completed, centrifuge and collect the PDA-PANI-Ti3C2T x The solid precipitate was washed to remove the unreacted dopamine hydrochloride, and finally the solid precipitate was dispersed in water to obtain PDA-PANI-Ti3C2T x Dispersion liquid; The amount of water used in step (3) is such that 1000 ml of water is added for every 1 g of precipitation; The amount of tromethamine used in step (3) satisfies the requirement that 5 L of dispersion liquid is used for every 6 g of tromethamine. The pH value in step (3) is adjusted to 8-9 by adding 0.1 mol / L hydrochloric acid; The reaction conditions described in step (4) are 12-48 h at 4°C; The amount of dopamine hydrochloride used in step (4) satisfies the requirement that 0.625-3.125 L of the mixed solution is used for every 1-5 g of dopamine hydrochloride; PDA-PANI-Ti3C2T described in step (4) x The dispersion is 1g PDA-PANI-Ti3C2T x The solid precipitate was dispersed in 250 ml of water; The PDA-PANI-Ti3C2T x The preparation method of the waterborne polyurethane anticorrosive coating comprises the following steps: PDA-PANI-Ti3C2T x The composite dispersion is added to the aqueous polyurethane emulsion and mixed evenly, and then industrial silica sol, defoamer, leveling agent and dispersant are added thereto and mixed evenly to obtain a PDA-PANI-Ti3C2T x Water-based polyurethane anti-corrosion coating.
2. A method according to claim 1 comprising using PDA-PANI-Ti3C2T x The water-based polyurethane anti-corrosion coating is characterized by: The waterborne polyurethane is waterborne polyurethane F0401; The leveling agent is AKN-151B; The dispersant is BYK-P104.
3. A PDA-PANI-Ti3C2T-containing material according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The concentration of hydrochloric acid in step (1) is 1 mol / L; the amounts of aniline monomer and hydrochloric acid are such that 0.1-0.4 g of aniline monomer is added to every 20 ml of hydrochloric acid; and the amounts of ammonium persulfate and hydrochloric acid are such that 0.3-1.2 g of ammonium persulfate is added to every 10 ml of hydrochloric acid.
4. A PDA-PANI-Ti3C2T-containing material according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: Ti3C2T described in step (2) x Dispersion refers to the Ti3C2T x Dispersed in water, and treated with ultrasound under N2 protection to obtain 2-4 g / L Ti3C2T x Aqueous dispersion; The aniline / HCl solution, ammonium sulfate / HCl solution and Ti3C2T x The volume ratio of the dispersion is 2:1:
10.
5. A PDA-PANI-Ti3C2T-containing material according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The static condition described in step (2) is to place at 0-8°C for 12-48 hours; The reaction conditions in step (2) are 0-8°C for 12-48 h; The washing described in step (2) refers to washing the precipitate with water or anhydrous ethanol.
6. A PDA-PANI-Ti3C2T-containing material according to claim 1 x The water-based polyurethane anti-corrosion coating is characterized by: The washing described in step (4) refers to washing the precipitate with water or anhydrous ethanol.
Citation Information
Patent Citations
Preparation method of anti-pollution protective paint
CN106811079A
Environmentally friendly efficient anti-corrosion water-based coating and synthesis method thereof
CN109054475A
Preparation method and application of modified anti-corrosion super-hydrophobic integrated coating
CN112300697A
Ti3C2TX (MXene) / polyaniline-containing water-based anticorrosive paint and preparation method thereof
CN112552801A
